2020
DOI: 10.1117/1.jmi.7.1.012707
|View full text |Cite
|
Sign up to set email alerts
|

Harmonization of radiomic features of breast lesions across international DCE-MRI datasets

Abstract: Purpose: Radiomic features extracted from medical images acquired in different countries may demonstrate a batch effect. Thus, we investigated the effect of harmonization on a database of radiomic features extracted from dynamic contrast-enhanced magnetic resonance (DCE-MR) breast imaging studies of 3150 benign lesions and cancers collected from international datasets, as well as the potential of harmonization to improve classification of malignancy.Approach: Eligible features were harmonized by category using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 16 publications
1
37
0
Order By: Relevance
“…Although promising results have been reported in the literature [35,36], these techniques require access to the images, unlike ComBat. The ComBat realignment method has been previously used in MR radiomic studies [20][21][22][23] without any explicit validation or investigation of the respective role of the image standardization and of the scanner/protocol effect compensation as studied here (Figures 1 and 2). In [20], authors reported an increased accuracy of Entropy extracted from apparent diffusion coefficient MR images to predict the locoregional control in cervical cancer after ComBat, fully consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although promising results have been reported in the literature [35,36], these techniques require access to the images, unlike ComBat. The ComBat realignment method has been previously used in MR radiomic studies [20][21][22][23] without any explicit validation or investigation of the respective role of the image standardization and of the scanner/protocol effect compensation as studied here (Figures 1 and 2). In [20], authors reported an increased accuracy of Entropy extracted from apparent diffusion coefficient MR images to predict the locoregional control in cervical cancer after ComBat, fully consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been used in MR radiomic studies [20][21][22][23], it has never been validated in that highly challenging context.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, all the data were obtained from one center with a single MRI machine, software and protocol, and our results need to be externally validated probably using a harmonization of radiomic features method such as the ComBat method (54). Fourth, we only performed a cross validation of our results due to the relatively small sample size (174 lesions).…”
Section: Discussionmentioning
confidence: 99%
“…The alternative would be a data‐driven approach. Such approaches exist; for example, by harmonizing given feature distributions, 39 or by harmonizing MR images using deep learning, from which features can then be calculated 40 . Our model‐based approach may have several advantages over data‐driven approaches.…”
Section: Discussionmentioning
confidence: 99%